Legalitas Akta Publisitas Pada Pendaftaran Badan Hukum Melalui Cyber Notary - Ivana Aulia Novita (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research departs from two legal issues, namely: 1) the regulation of legal entities regarding registration of legal entities via cyber notary, and 2) the strength of proof of publicity deeds on registration of legal entities via cyber notary. This research method uses an empirical juridical approach. Data was collected through interviews and literature study. Interviews were conducted with notaries who practice cyber notary, while literature studies were carried out by reviewing legal materials, namely UUJN, ITE Law, Limited Liability Company Law. and Regulation of the Minister of Law and Human Rights which regulates the Procedures for Submitting Applications for Legalization of Legal Entities and Approval of Amendments to the Articles of Association as well as other related laws and regulations. The results show: First, the statutory regulations regarding registration of legal entities via cyber notary are based on UUJN article 15 paragraph (3) which states that Notaries can be given other powers according to statutory regulations. The Law on Limited Liability Companies mandates the registration of legal entities through an electronic system by appointing implementing regulations under it, namely PP and Ministerial Regulations. In the Regulation of the Minister of Law and Human Rights which provides limited legality for cyber notaries only in the case of applications for the use of the name of a legal entity, applications for ratification of a legal entity, and requests for the announcement of a legal entity as well as ratification of changes to the articles of association of a Limited Liability Company. Second, the publicity deed for registering a legal entity via a cyber notary has strong and perfect evidentiary power as seen from UUJN Article 15 paragraph (3) and Permenkumham No. 2 of 2016 which regulates registration through the Legal Entity Administration System, hereinafter abbreviated as SABH as the agency administration service system. law electronically.